ANALISIS FAKTOR YANG MEMPENGARUHI INTENSI TERHADAP PELAKSANAAN DISCHARGE PLANING BERDASARKAN THEORY OF PLANNED BEHAVIOR (TPB) - Widiharti Widiharti; Diah Jerita Eka Sari (Fakultas Keperawatan, Universitas Riau, 2023)
Discharge planning is a process of assessing complaints and patient management carried out by nurses from entering to leaving the hospital. In fact, nurses generally only carry out discharge planning activities when patients are going home or leaving the hospital. This may happen because nurses do not understand the mechanism of discharge planning or precisely because the workload of nurses is too great. The purpose of this study was to analyze the factors that influence the intention to carry out discharge planning in nurses based on the Theory of Planned Behavior (TPB). Observational research is analytic, with a cross-sectional approach. The research population includes all room nurses and sample 90 nurses. Sampling uses probability sampling using a simple random sampling approach. The instrument uses a questionnaire, data analysis uses the lambda test. The analysis shows a relationship between knowledge and attitude, with a value of p = 0.000 (p≤0.05). There is a correlation between knowledge and norms p=0.000 (p≤0.05). There is a correlation between Knowledge and Perceived Behavior Control of nurses in carrying out discharge planning p=0.000 (p≤0.05), there is no correlation between attitude and intention p=0.353 (P≥0.05), there is no correlation between norms and intentions p=0.147 (P≥0.05), there is no correlation between Perceived Behavior Control with intention p=0.061 (P≥0.05). Nurses’s knowledge is directly relate to attitudes, norms, Perceived Behavior Control, and nurses intentions toward the implementation of discharge planning